1997
DOI: 10.1002/chin.199742340
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthetic Strategies in Combinatorial Chemistry

Abstract: Synthetic Strategies in Combinatorial Chemistry -(38 refs.). -(SPALLER, M. R.; BURGER, M. T.; FARDIS, M.; BARTLETT, P. A.; Curr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…A review article from 1997 by Spaller et al suggested that combinatorial libraries may be suggested to fall into two categories: focused libraries, where a number of closely related compounds based on a privileged structure are synthesized with a known target in mind, and prospecting libraries, where an entirely new lead compound is sought, so the objective is to screen a large number of structurally varied compounds in the hope of finding a lead with a novel mode of action [29]. The focused libraries can be considered to be the result of a "classical" combinatorial chemistry approach, and further reference made here to combinatorial chemistry refers to the synthesis of this type of library.…”
Section: Small Molecules and Biologymentioning
confidence: 99%
“…A review article from 1997 by Spaller et al suggested that combinatorial libraries may be suggested to fall into two categories: focused libraries, where a number of closely related compounds based on a privileged structure are synthesized with a known target in mind, and prospecting libraries, where an entirely new lead compound is sought, so the objective is to screen a large number of structurally varied compounds in the hope of finding a lead with a novel mode of action [29]. The focused libraries can be considered to be the result of a "classical" combinatorial chemistry approach, and further reference made here to combinatorial chemistry refers to the synthesis of this type of library.…”
Section: Small Molecules and Biologymentioning
confidence: 99%
“…The increasing significance of combinatorial chemistry in pharmaceutical and material sciences is well recognized, which demands the development of new strategies to generate a collection of analogues of interesting compounds . It is well documented that imidazole or benzoimidazole derivatives are of particular interest for drug discovery since they are known to elicit a broad spectrum of biological activities, and their applications in diverse therapeutic areas (including antivirals, antitumor, antifungals, etc) have been discovered .…”
Section: Introductionmentioning
confidence: 99%